Optimization of Micro-Learning-Based Digital Content: An Effectiveness Analysis of Short Videos in Mathematics Learning - Iyan Nurhasni Ahya; Muh El-Basyari Hartono; Imam Makruf (Doctoral Program of Social Science Pasundan University, 2026)
In the digital era of 2026, mathematics remains a subject that triggers high levels of academic anxiety (math anxiety), while students’ attention spans continue to decline due to the dominance of social media. This study aims to analyze the effectiveness of micro-learning strategies through short-form video content (60–90 seconds) as an instrument for reducing cognitive load and increasing student engagement in mathematics learning. This study employed a Systematic Literature Review (SLR) method on 20 selected scholarly sources published between 2021 and 2026, focusing on educational technology, cognitive psychology, and the implementation of artificial intelligence (AI). The analysis revealed that the atomization of mathematics materials into short-video formats significantly increased content completion rates up to 85% and reduced student stress levels through the provision of informal self-paced learning environments. The integration of AI-powered dynamic visualization and Math Hacks techniques proved effective as cognitive scaffolding that enhances students’ self-efficacy. This article concludes that the adaptation of concise and visual digital content is no longer merely an option but a pedagogical necessity to maintain the relevance of mathematics curricula in the post-digital era.